Microstructure and tribological properties of WC-12Ni/Cu composite coating prepared by laser cladding on 45 steel surface - Fulong Zhang; Junquan Zhang; Lu Ping; Zhang Wentao; Shuangyu Liu; Huang Chuanjin; Zhang Qiushi; Bo Cui; Wang Binhua (Materials Research Express)
To reduce the amount of copper used and improve the service life of the copper layer in the plunger pair of a plunger pump, Ni15 was chosen as the transition layer to assist in the laser cladding preparation of copper-steel composite materials. WC-12Ni powder was mixed into Cu powder at concentrations of 5, 10, 15, 20, 25 wt%, and different compositions of cladding layers were prepared using laser cladding technology. The microstructure of the cladding layers was analyzed by optical microscopy (OM), scanning electron microscopy (SEM), and energy dispersive x-ray spectroscopy (EDS). The microhardness of the composite coatings was tested using microhardness Vickers (MHV), and the tribological performance of the composite coatings was evaluated using the friction and wear testing machine (F&WM). The results showed that, in terms of microstructure, element diffusion occurred around the WC particles, and partial dissolution of WC particles at their sharp corners led to the formation of new compounds with other elements. Additionally, WC particles contributed to the refinement of the microstructure. In terms of performance, the microhardness of the composite coatings increased with the increase in WC-12Ni content, reaching a maximum of 412.5 HV _0.1 when the content was 25 wt%. Regarding tribological properties, the composite coating with 20 wt% WC-12Ni exhibited excellent friction-reducing properties, with a stable coefficient of friction of 0.53. Both the 20 wt% and 25 wt% WC-12Ni composite coatings demonstrated good wear resistance, with wear rates of 4.4 × 10 ^−4 mg/ N·m.